Pragmatic Literary Stylistics
IX, 229 p.
Keywords: In considering the ways in which current theories of language in use and communicative processes are applied to the analysis, interpretation and definition of literary texts, this book sets an agenda for the future of pragmatic literary stylistics and provides a foundation for future research and debate.